EFFICACY OF EMOTIONAL INTELLIGENCE TECHNIQUE AND PARENTAL SOCIAL CLASS IN FOSTERING VOCATIONAL DEVELOPMENT OF SECONDARY SCHOOL STUDENTS IN GOMBE STATE, NIGERIA - Olanrewaju, Muraina Kamilu; Suleiman, Yusuf (International Journal of Education, 2019)
This study focused on efficacy of emotional intelligence technique and parental social class in fostering vocational development of secondary school students in Gombe State, Nigeria. Pretest-posttest, control group quasi-experimental design with a 2x3 factorial matrix was used in the study. Multi-stage sampling technique was used in sampling 117 participants from 3 local government areas (12 schools) in the state. The respondents were measured with validated scale of 0.79 reliability coefficient and the data obtained was analyzed using T-test and Analysis of Variance statistical analysis. Two (2) research hypotheses were formulated and tested at 0.05 level of significance. The results showed that there was significant difference in the vocational development of secondary school students exposed to emotional intelligence technique and those in the control group (t= 57.64; p0.05) and there was significant difference in the vocational development of secondary school students with high, moderate and low parental social class (t= 27.51; p0.05). In view of these findings, the study recommended that educational stakeholders should intensify their effort to organize conferences on the implications of emotional intelligence technique and parental social classes on effective re-orientation of youths towards improving vocational development.